A Review of Movement Exaggeration Techniques to Enhance the Precision Identification for Minute Facial Feelings - Jyothirmai, M; Sree Chandana, Y V; Vishnu Vardhan, C (International Journal of Computer Sciences and Engineering, 2025)
Acknowledgment of regular feelings from human countenances is an interesting point with a number of potential applications like human-framework connection, computerized frameworks, image and video recovery and similar development platforms. Much research has already been done in this area and there is scope for further improvement. Comparison was done for four different algorithms based on accuracy of recognition rate. The goal is to achieve improvement compared to previous algorithms. By using PCA-SIFT the accuracy was improved between 6%-18%.